SHIFTING DAKWAH METHODS TO MATCH MEDIA TECHNOLOGY TRANSFORMATION: The Case of Nahdlatul Ulama, Muhammadiyah, and Al Washliyah - Murodi, Murodi; Muhtadi, Muhtadi; Kamarusdiana, Kamarusdiana; Darajat, Deden Mauli (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
The advancement of communication technology has sophisticated all aspects of human lives, including Islamic dakwah (preaching) activities, for Muslim communities in Indonesia. As a result, several Islamic organizations in Indonesia try hard to match this advancement by using digital media for their dakwah to reach larger audiences and youth media-savvy generation. This article, by focusing on three Islamic organizations in Indonesia (Nahdlatul Ulama known as NU, Muhammadiyah, and Al Washliyah), addresses the question of how their dakwah activities and strategies respond to advancement of communication technology on a social media platform, YouTube. This study employs digital etnography by collecting the data from YouTube accounts affiliated to the three organizations. By using content analysis for data interpretations, this article finds that each Islamic organization has its own characteristics of virtual dakwah activities and strategies. NU focuses on the teachings of ahlussunnah wal jamaah and religious tolerance, Muhammadiyah emphasizes charity and business, while Al Washliyah aims to strengthen the faith and morals of the society. In addition, their virtual dakwah activities are also in the context of countering transnational Islamic movements that utilize social media for their dakwah.